AJARAN KEPEMIMPINAN HINDU DALAM MEMBENTUK KARAKTER PEMIMPIN BANGSA - Kadek Wahyu Prasetya; I Nyoman Sueca; I Ketut Madja (UHN IGB Sugriwa Denpasar, 2020)
The leader is a person who moves early, goes ahead, takes the first step, pioneers, directs, guides, moves others through their influence. But nowadays the the rampant corruption cases that occured in indonesia, caused due to the abuse of power given by the community to leaders who are concerned with individuals only. This happened because of a lack of understanding of a leader regarding character education, ethics and morality in leadership. This paper was made, aiming to instill the importance of forming the character of a leader in order for a leader to be able to carry out his tasks to be a good leader. Hindu has the concept of leadership contained in the Nitisastra and ancient leadership of the archipelago in which teaches about the characteristics and character that should be owned by a leader. The aim is to adopt the character of leadership in the teachings which is expected to form a good character of the nation's leaders.